ANALISIS PEMIKIRAN IBNU KHALDUN DALAM KOMUNIKASI DAN HEGEMONI POLITIK PEREMPUAN DI INDONESIA - Tanjung, Taufiq Hidayah; Zulkarnain, Iskandar; Mailin, Mailin (Journal of Gender and Social Inclusion in Muslim Societies, 2023)
This study aims to explore the ideas of Ibn Khaldun, particularly his concept of asabiyyah (group solidarity), in the context of political communication and hegemony in Indonesia. Using a descriptive qualitative approach, the research investigates the relevance of Ibn Khaldun’s theories to the contemporary political dynamics of Indonesia, which are often influenced by social solidarity in the preservation of political power. The research methodology employed is library research, where data is collected from various sources including books, academic journals, and articles that discuss Ibn Khaldun’s political theories and their application in Indonesia. The data analysis technique used is byat analysis, which involves categorizing and interpreting the data to identify similarities and differences in the viewpoints presented. The findings of this study indicate that Ibn Khaldun’s notion of asabiyyah, or group solidarity, offers valuable insights into the patterns of political communication and hegemony in Indonesia. The strength of social solidarity among groups, whether based on religion, ethnicity, or ideology, plays a crucial role in the stability and continuation of political power in the country. The research also reveals that overly dominant political communication within one group can potentially lead to social tensions, aligning with Ibn Khaldun’s view that power based on the domination of a particular group will not endure for long. This theory provides a relevant perspective for understanding identity politics and social dynamics in contemporary Indonesia.